Efficacy and safety of iguratimod in the treatment of rheumatic and autoimmune diseases: a meta-analysis and systematic review of 84 randomized controlled trials - Zeng, Liuting; He, Qi; Deng, Ying; Li, Yuwei; Chen, Junpeng; Yang, Kailin; Luo, Yanfang; Ge, Anqi; Zhu, Xiaofei; Long, Zhiyong; Sun, Lingyun (Frontiers in Pharmacology, 2023)
Objective: To evaluate efficacy and safety of iguratimod (IGU) in the treatment of rheumatic and autoimmune diseases.Methods: Databases such as Pubmed, Embase, Sinomed were searched (as of July 2022) to collect randomized controlled trials (RCTs) of IGU in the treatment of rheumatic and autoimmune diseases.Two researchers independently screened the literature, extracted data, assessed the risk of bias of the included literature, and performed meta-analysis using RevMan 5.4 software.Results: A total of 84 RCTs and 4 types of rheumatic and autoimmune diseases [rheumatoid arthritis (RA), ankylosing spondylitis (AS), primary Sjögren's syndrome (PSS) and Autoimmune disease with interstitial pneumonia]. Forty-three RCTs reported RA and showed that IGU+MTX therapy can improve ACR20 (RR 1.